Forensic interpretation of molecular variation on networks of disease transmission and genetic inheritance. Issue 21 (7th October 2014) - Velsko, Stephan P.; Osburn, Joanne; Allen, Jonathan; McCord, Bruce
<x xml:space="preserve">Abstract</x> This paper describes the inference‐on‐networks (ION) framework for forensic interpretat ION of molecular typing data in cases involving allegations of infectious microbial transmission, association of disease outbreaks with alleged sources, and identifying familial relationships using mitochondrial or Y chromosomal DNA. The framework is applicable to molecular typing data obtained using any technique, including those based on electrophoretic separations. A key insight is that the networks associated with disease transmission or DNA inheritance can be used to define specific testable relationships and avoid the ambiguity and subjectivity associated with the criteria used for inferring genetic relatedness now in use. We discuss specific applications of the framework to the 2003 severe acute respiratory syndrome (SARS) outbreak in Singapore and the 2001 foot‐and‐mouth disease virus (FMDV) outbreak in Great Britain.